YouTube Platform in Teaching and Learning Constructions of Geometric Figures - Senad Orhani (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This scientific paper aims to investigate the impact of the YouTube platform on the teaching and learning of constructions of geometric figures. The YouTube platform is an online video-sharing environment that has gained widespread popularity due to the versatile and diverse content it offers. In this study, we analyze the use of the senadorhani YouTube channel in the context of teaching geometry and the construction of geometric figures. The study includes the benefits and challenges that the use of this platform brings to the process of teaching and learning the constructions of geometric figures. The purpose of this scientific paper is to investigate the potential and influence of the YouTube platform in teaching and learning the constructions of geometric figures. To carry out this research, a methodology based on the content analysis of the YouTube platform has been chosen. The sample was selected by the students of the “Heronjtë e Lumës”, “Dëshmorët e Vërrinit”, “Zef Lush Marku”, “Samidin Emini” and “Lidhja e Prizrenit” schools. The sample is represented by students of classes VI-IX with a total of 106 students. A range of appropriate methods were used to collect the data for this study. These include student surveys, qualitative interviews, and content analysis on the YouTube platform. The results show that YouTube offers a wide range of geometry learning content, including demonstrations, tutorials, and detailed explanations. This research assesses that the use of YouTube has great potential to improve the teaching and understanding of constructions of geometric figures.